Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approac hes to development over the last 30 years, most aid infrastructure con tinues to concentrate on the design and subsequent implementation of c losed models. This article does not propose an alternative to blueprin ts, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a s upplementary management and learning approach which enables implemente rs to be dynamic, adaptive, and responsive to problems and opportuniti es. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.